Correlation between neutrophil to lymphocyte ratio and early renal function level in elderly diabetic patients - SUN Ming-yu; GAO Po; ZHANG Shi-yang; HAN Yong-sheng (Linchuang shenzangbing zazhi)
Objective To explore the correlation between neutrophil to lymphocyte ratio(NLR) and early renal function levelin elderly patients with type 2 diabetes. Methods A total of 346 elderly diabetic patients hospitalized in Department of Endocrinology and Department of Gerontology in The First Affiliated Hospital of USTC from June 2018 to January 2019 were enrolled in this study.Generalclinical data such as age,gender, body mass index,NLR, urinary albumin excretion(UAE) in patients with different estimated glomerular filtration rate(eGFR) levels were compared and analyzed. Logistic regression analysis was used to evaluate the effect of each confounding factor on eGFR using eGFR as an objective variable. Pearson’s correlation coefficients were used to test the associations between various variables and eGFR. Results Age, risk of cardiovascular diseases, use of antihypertensive medication, serum uric acid(SUA) and NLR were higher in correlation with decreased eGFR, but DBP, HDL-C, and HbA1 c were lower. with the statistically significant difference(P<0.05). NLR was negatively related to eGFR. Multiple linear regression analysis using eGFR as objective variable indicated that NLR(β=-0.101,P=0.009) as well as age(β=-0.525,P<0.001), body mass index(β=-0.083,P=0.036), serum uric acid(β=-0.360,P<0.001), and use of medication against SUA(β=-0.128,P=0.001)were significantly and independently associated with eGFR. Conclusions NLR is an effective evaluation index for early renal function in elderly patients with type 2 diabetes,which is easy and convenience for clinical use.